2008
DOI: 10.1136/oem.2007.036327
|View full text |Cite
|
Sign up to set email alerts
|

Lung and other cancer site mortality in a cohort of Italian cotton mill workers

Abstract: The results support previous reports that a high and prolonged exposure to cotton dust and other endotoxin-containing organic dusts is related to a lower risk of lung cancer. There was no indication of a reduced risk for other forms of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
1
22
0
3
Order By: Relevance
“…In addition to farmers and gardeners, fishermen appear to some extent to be protected against cancers [30]. Cotton textile workers are less likely to develop lung cancers as compared to the general populations [31], and one study suggests that this may also be the case for sewage plant workers [32]. A study on all economically active Finns identified in a population census in 1970, followed for 30 million-person years, revealed that heavy exposure to moulds and bacteria in the working environment was associated with reduced lung cancer risk among men [33].…”
Section: Microbes and Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to farmers and gardeners, fishermen appear to some extent to be protected against cancers [30]. Cotton textile workers are less likely to develop lung cancers as compared to the general populations [31], and one study suggests that this may also be the case for sewage plant workers [32]. A study on all economically active Finns identified in a population census in 1970, followed for 30 million-person years, revealed that heavy exposure to moulds and bacteria in the working environment was associated with reduced lung cancer risk among men [33].…”
Section: Microbes and Cancermentioning
confidence: 96%
“…Accumulating data obtained from several lines of evidence suggest that cancers occur less frequently 1. Among people who are, by occupation, heavily exposed to environmental micro-organisms [25][26][27][28][29][30][31][32][33] 2. Among populations that adhere to a traditional lifestyle [34] 3.…”
Section: Microbes and Cancermentioning
confidence: 99%
“…They permit to suppose that the lower risk of cancer among people working in environments polluted with bacterial endotoxin versus the general population (18,19), different levels of malignancies in humans working in the same carcinogenic conditions (20) and cases of spontaneous regression of cancer (21,22) are dependent on the level of IgMNAE in a person's blood. The low IgMNAE level in the blood may be an endogenous indicator of a high risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Jis prasiskverbia į organizmą. Mažesnis mirtingumas yra aiškinamas endotoksino apsauginiais mechanizmais aktyvinant imuninius procesus [26][27][28][29][30].…”
Section: įVadasunclassified
“…Atavistinio endotoksino patogenetinį ryšį su navikinio proceso formavimosi mechanizmais parodo ir jau minėti epidemiologiniai darbai su egzogeniu endotoksinu, esančiu medvilnės ir lino pramonės darbininkų ir žemės ūkio darbuotojų aplinkoje [26][27][28][29][30]. Fenomenas, kad žmogaus aplinkoje esantis endotoksinas, patekęs į organizmą, mažina riziką susirgti vėžiu, patvirtina mūsų apibendrinimą apie IgMNAE įtaką onkologinių ligų mažėjimui ir nurodo būtinumą stiprinti žmonių populiacijos natūralų imunitetą atavistiniam endotoksinui.…”
Section: Išvados Ir Pasiūlymaiunclassified